Slang translation: A case study of the strategies applied in English – Vietnamese translation of J.D. Salinger’s “The catcher in the rye” by Phung Khanh = Nghiên cứu chiến lược dịch từ lóng từ Anh sang Việt của dịch giả Phùng Khánh trong tác phẩm “Bắt trẻ đồng xanh” - Trần, Bùi Phương Dung (2020)
Slang has always been an obstacle in translation due to its cultural specific features. Its translation requires great comprehension, research, and creativity to fully render the desirable effect, meaning and even text form. However, the matter of translating slang from English to Vietnamese, especially in literary work, has not received appropriate attention. It is useful to discuss and have further insight into how translators apply translation strategies and deal with slang. As a result, the aim of this study is to analyze the characteristics of slang, and investigate on how translation strategies were used to render slangs in general as well as in specific types of slang. A novel by J.D.Salinger “The Catcher in the Rye” and its Vietnamese translation by Phung Khanh were chosen as the subjects of the study. The study adopted Mattiello’s slang classification to categorize 100 purposed sampling slangs from the novel. The focus of the research lay on the translation strategies, which were investigated based on a set of 5 strategies: substitution (Garcarz, 2011); compensation (Blonskyte & Petroniene, 2013); omission (Baker, 1998; Garcarz, 2011; Blonskyte & Petroniene, 2013); substitution ( Garcarz, 2011); description (Baker, 1998; Garcarz, 2011); softening (Blonskyte & Petroniene, 2013; Drozde, Vogule, 2008). The research calculated the density of the five mentioned translation strategies to demonstrate the use of these strategies in Vietnamese translation. The result showed that the prevalent strategy in the translation of the English slang in “The catcher in the rye” into Vietnamese is substitution and compensation